Invasive cutaneous mucormycosis: A case report on a deadly complication of a severe burn. (2022) - Welch, Geoffrey; Sabour, Andrew; Patel, Kushal; Leuthner, Kimberly; Saquib, Syed F.; Medina-Garcia, Luis
Abstract: A 38 year old woman presented with burns totaling 45 % total body surface area, following an explosion resulting from manufacturing cannabis wax. Initial debridement, was delayed to hospital day 7 due to hemodynamic instability. Over the course of her, hospitalization, she required multiple debridements and grafting to her lower, extremities; grafted tissue never survived longer than 72 h. Her bilateral lower, extremities began to exhibit visible mold growth. She underwent repeated, debridements down to vitalized tissue only for recurrent necrosis and mold growth to, occur. She underwent serial amputations eventually reaching the level of her midthigh, At this point her clinical condition deteriorated further resulting in multiorgan failure., Ultimately family made the decision to remove her from life support, and she expired, within a few hours. Postmortem analysis identified Rhizopus spp, Fusarium spp, and, Geotrichum candidum. Mucormycosis species are a frequent infector of Cannabis, sativa, which our patient was working with in the inciting explosion. Cutaneous, mucormycosis is a documented but rare manifestation. We propose that the patient's, relatively young age, severity of burns, and exposure to cannabis plants resulted in this, unusual presentation